ACOMPANHAMENTO DE ENFERMAGEM A UM PACIENTE HOSPITALIZADO, DEPENDENTE DE CRACK - Stumm, Eniva M. F.; Menin, Gisele E.; Oliveira, Daiane d.; Frohlich, Mariana; Cruz, Cibele T. d. (Salão do Conhecimento, 2013)
Resumo